2017
DOI: 10.1016/j.soard.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Early improvement in obstructive sleep apnea and increase in orexin levels after bariatric surgery in adolescents and young adults

Abstract: Background Obstructive sleep apnea (OSA) associated with obesity is known to improve after bariatric surgery, but little is known about early changes in this condition following surgery. Objectives To study the clinical course of OSA after bariatric surgery. Setting Children's hospital in the United States. Methods Adolescents and young adults with obstructive sleep apnea undergoing vertical sleeve gastrectomy (n=6) or gastric bypass (n=1) were enrolled in this prospective study. Participants underwent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Moreover, Cigdem et al showed that laparoscopic gastric band application resulted not only in significant weight loss but also in decreased Orexin-A serum levels [ 51 ]. Amin et al demonstrated a rise in Orexin and a decrease in leptin in a cohort of obese subjects affected by obstructive sleep apnea, after bariatric surgery, showing that metabolic changes were also occurring in the same time span and thus it was plausible that physiologic rather than anatomic changes may underlie the clinically significant improvement in obstructive sleep apnea as early as 11 days following bariatric surgery [ 52 ]. The regulation of Orexin and the involvement of the nervous system both depend on mechanical factors but also on chemical mediators and hormones that are in circulation after the intervention.…”
Section: Effects Of Bariatric Surgery On Adiponectin and Orexin-amentioning
confidence: 99%
“…Moreover, Cigdem et al showed that laparoscopic gastric band application resulted not only in significant weight loss but also in decreased Orexin-A serum levels [ 51 ]. Amin et al demonstrated a rise in Orexin and a decrease in leptin in a cohort of obese subjects affected by obstructive sleep apnea, after bariatric surgery, showing that metabolic changes were also occurring in the same time span and thus it was plausible that physiologic rather than anatomic changes may underlie the clinically significant improvement in obstructive sleep apnea as early as 11 days following bariatric surgery [ 52 ]. The regulation of Orexin and the involvement of the nervous system both depend on mechanical factors but also on chemical mediators and hormones that are in circulation after the intervention.…”
Section: Effects Of Bariatric Surgery On Adiponectin and Orexin-amentioning
confidence: 99%
“…Youth should be Tanner 4–5 in pubertal development and have achieved at least near final height 17 . The most common procedures used in children and associated with significant weight loss and improvement in metabolic control are: Roux-en-Y gastric bypass, sleeve gastrectomy, or laparoscopic adjustable gastric banding 188,193–195 . Post-surgical weight loss is often variable but usually ranges between 20–50% of initial body weight.…”
Section: Cardiovascular Risk Reductionmentioning
confidence: 99%
“…The arcuate nucleus of the hypothalamus is one of the main regulating organs for appetite. Studies have shown that many brain neurotransmitters, including dopamine and serotonin, and various neuropeptides, including neuropeptide Y (NPY), leptin, orexin A, ghrelin, growth hormone releasing factor, leptin, and glucagon-like peptide-1 (GLP-1), can affect the appetite [18][19][20][21][22]. Neurotransmitters and neuropeptides undergo changes during and after the process of SG, which in turn affect the appetite and food intake.…”
Section: Reduced Food Intakementioning
confidence: 99%